2021
DOI: 10.1080/23311932.2021.1879715
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of market participation decision by smallholder haricot bean (phaseolus vulgaris l.) farmers in Northwest Ethiopia

Abstract: Current knowledge on product marketing in Ethiopia is poor and inadequate for designing and implementing policies to overcome problems in the marketing system. This study was conducted to identify the factors influencing the market participation decision of smallholder haricot bean (Phaseolus vulgaris L.) farmers in Northwest Ethiopia. Survey data were collected from 312 smallholder farmers and analyzed using Heckman's two-step econometric model that estimates probit model in the first step and regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
3
6
0
1
Order By: Relevance
“…This signifies that the more the family dependents, the less the respondents are likely to transition their apiculture activities to modern. The finding is consistent to that of Andaregie et al (2021) who found household size negative and greatly significant on adoption of modern apiculture. Equally, Mulatu et al (2021) found that majority of apiculture farmers with larger families are non-adopters of technology.…”
Section: Multiple Linear Regression Results On Adoption Of Modernsupporting
confidence: 90%
“…This signifies that the more the family dependents, the less the respondents are likely to transition their apiculture activities to modern. The finding is consistent to that of Andaregie et al (2021) who found household size negative and greatly significant on adoption of modern apiculture. Equally, Mulatu et al (2021) found that majority of apiculture farmers with larger families are non-adopters of technology.…”
Section: Multiple Linear Regression Results On Adoption Of Modernsupporting
confidence: 90%
“…Gambar 6 menunjukkan bahwa saluran pemasaran yang beragam menyebabkan usaha hortikultura bisa bertahan. Hal ini sesuai dengan penelitian sebelumnya yang menyatakan aspek yang menjamin keberlanjutan usaha hortikultura adalah kepastian pasar dan harga yang memberikan keuntungan yang relatif stabil (Amao & Egbetokun, 2018;Andaregie et al, 2021). Oleh karena itu untuk meningkatkan daya tahan usaha hortikultura maka dibutuhkan kemampuan pengusaha untuk memperbanyak akses untuk menjual langsung kepada konsumen dalam berbagai bentuk baik produk segar maupun olahan (Reddy et al, 2019;Udaykumar et al, 2020).…”
Section: Pasarunclassified
“…This could be because farmers selected traits found only in local varieties or because acceptable varieties for their agro-ecological settings were unavailable. It could also be attributed to institutional variables, such as the policy environment, which have an impact on the availability of inputs (land, labor, seeds, and fertilizer), as well as credit and production markets [26].…”
Section: Farmers' Adoption Decisionmentioning
confidence: 99%